Time on the Crossing: Emigrant Voyages across the Atlantic, 1853 to 1913 - Timothy J. Hatton (Institute of Labor Economics (IZA), 2023)
I provide a new series of the average duration of emigrant voyages from Liverpool to New York from 1853 to 1913. Time on the crossing fell by 80 percent, from about 40 days to just eight, most of which occurred in the first two decades and was associated with the transition from sail to steam. The standard deviation of voyage durations also dramatically decreased. Although average transatlantic fares did not fall, if foregone earnings during the voyage are included, the total cost declined until the early 1900s, and especially so when measured in terms of the number of week's work.
Keywords: F22; O33; N73; 330; steam ships; transatlantic migration; voyage times